Future Edge; and, Instructional Message Design: Principles from the Behavioral and Cognitive Science (Second Edition) - James W. King (Journal of Applied Communications, 1993)
Book reviews of Future Edge by Joel Arthur Baker; and Instructional Message Design: Principles from the Behavioral and Cognitive Science, (Second Edition), edited by M. Fleming and W.H. Levie.